Perceived Parental Stress and Emotional Intelligence as Predictors of Parenting Styles among Married Couples - Babatunde O. Olubori; Esohe G. Ehondor; Olubunmi O. James; Emmanuel E. Uye (Cita konsultindo, 2025)
Parenting is a multifaceted journey filled with joys, challenges, and responsibilities that significantly affect the well-being of both parents and children. Studies that investigated parenting styles have used different predictors with results giving varied results. This study examines the predictability of perceived parental stress and emotional intelligence on parenting styles among married couples in Ibadan, Nigeria. Cross-sectional survey design was adopted while purposive sampling technique was used to select the study population. Data were collected from 393 participants using validated questionnaires and analyzed using t-test of independent samples and multiple regressions. Two hypotheses were tested and accepted at p <.05 level of significance. The results revealed that perceived parental stress and emotional intelligence jointly predicted parenting styles [R2=.06, F(5,392)= 4.58, p <.05]. In addition, the result indicated that regulation of emotional appraisal (β = 15, t = 2.45, p <.05) and use of emotion (β =.15, t = 2.58, p <.05) dimensions of emotional intelligence independently predicted parenting styles. Finally, gender significantly influenced parenting styles [t(391)= 2.11, p <.05] such that male participants reported higher perceived parenting styles (M= 91.37, SD = 22.49) compared to their female counterparts (M = 87.22, SD= 16.29). The study concluded that perceived parental stress and emotional intelligence are strong predictors of parenting styles among study participants. It is recommended that stress management programs should be put in place to help parents reduce stress levels to improve their ability to provide better parenting care to their children.